Diversity in organizations a critical examination - Herring, Cedric; Henderson, Loren (Routledge Taylor & Francis, 2015)
Diversity in Organizations argues that ensuring a diverse workforce composition has tangible benefits for business organizations. Rather than relying on touchy-feely arguments, Herring and Henderson present compelling evidence that directly links diversity to the bottom line. However, the book goes beyond merely arguing that we should embrace diversity because it is profitable; it shows that the true power of diversity lies in its potential as a catalyst and incubator for innovation